2012
DOI: 10.3109/03639045.2012.662510
|View full text |Cite
|
Sign up to set email alerts
|

Galactose decorated PLGA nanoparticles for hepatic delivery of acyclovir

Abstract: The present study explores prospective of surface tailored nanoparticles for targeted delivery of acyclovir along with the interception of minimal side effects. Acyclovir loaded plain and galactosylated poly lectic co glycolic acid (PLGA) nanoparticles were efficiently prepared and characterized by Fourier transform infrared spectroscopy, scanning electron microscopy (SEM), size, polydispersity index, zeta potential, and entrapment efficiency. The formulations were evaluated for in vitro drug release and hemol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…Biodistribution studies were performed to assess the targeting ability of galactosylated nanoparticles to deliver tacrolimus to the hepatic tissues. The concentration of tacrolimus in liver was significantly higher in nanoparticle formulations than plain drug, which may be due to uptake of nanoparticles by mono‐nuclear phagocytic system [11]. However, the concentration in nanoparticles was significantly less than galactosylated PLGA nanoparticles ( P < 0.05) that might be due to non‐specific entry in the absence of specific receptors.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Biodistribution studies were performed to assess the targeting ability of galactosylated nanoparticles to deliver tacrolimus to the hepatic tissues. The concentration of tacrolimus in liver was significantly higher in nanoparticle formulations than plain drug, which may be due to uptake of nanoparticles by mono‐nuclear phagocytic system [11]. However, the concentration in nanoparticles was significantly less than galactosylated PLGA nanoparticles ( P < 0.05) that might be due to non‐specific entry in the absence of specific receptors.…”
Section: Resultsmentioning
confidence: 92%
“…The concentration of tacrolimus in liver was significantly higher in nanoparticle formulations than plain drug, which may be due to uptake of nanoparticles by mono-nuclear phagocytic system. [11] However, the concentration in nanoparticles was significantly less than galactosylated PLGA nanoparticles (P < 0.05) that might be due to non-specific entry in the absence of specific receptors. At 24 h, there was an increase in tacrolimus concentration from Tac-Gal-PLGA NPs by 4.83 fold and 11.72 fold from Tac-PLGA NPs and plain drug solution respectively.…”
Section: Biodistribution Studiesmentioning
confidence: 89%
See 2 more Smart Citations
“…Additionally, it protects the drug molecule from degradation and exhibits sustained release [36]. Most importantly, PLGA-based NPs are able to target particles to specific organs or cells [37,38], and have been widely used as drug delivery systems for the treatment of different pathologies. A large number of studies have demonstrated applications of PLGA-based delivery nanosystems in vaccination [39,40], cancer treatment [41,42], inflammation [43], and regenerative medicine [44].…”
Section: Nanomedicinesmentioning
confidence: 99%